Evolution of Artistic and Athletic Propensities: Testing of Intersexual Selection and Intrasexual Competition - Varella, Marco Antonio Correa; Štěrbová, Zuzana; Bártová, Klára; Fisher, Maryanne L.; Valentova, Jaroslava Varella (Frontiers in Psychology, 2022)
Since Darwin proposed that human musicality evolved through sexual selection, empirical evidence has supported intersexual selection as one of the adaptive functions of artistic propensities. However, intrasexual competition has been overlooked. We tested their relative importance by investigating the relationship between the self-perceived talent/expertise in 16 artistic and 2 sports modalities and proxies of intersexual selection (i.e., mate value, mating and parenting efforts, sociosexuality, and number of sexual partners) and intrasexual competition (i.e., aggressiveness, intrasexual competitiveness) in heterosexuals. Participants were 82 Brazilian men, 166 Brazilian women, 146 Czech men, and 458 Czech women (Mage=26.48, SD=7.12). Factor analysis revealed five factors: Literary-arts (creative writing, humor, acting/theatre/film, poetry, storytelling), Visual-arts (painting/drawing, sculpting, handcrafting, culinary arts, architecture design), Musical-arts (playing/instruments, singing, dance, whistling), Circus-arts (juggling, acrobatics), and Sports (individual and collective). Multivariate GLM showed more associations of the arts to intersexual selection in women and to intrasexual selection in men, and overall more relationships in women than in men. In women, literary and musical-arts were related to elevated inter- and intrasexual selections proxies, visual and circus-arts were related to elevated intersexual selection proxies, and sports were related to intrasexual selection proxies. In men, literary-arts and sports were related to elevated inter- and intrasexual selection proxies, musical-arts were related to intrasexual proxies, and circus-arts were related to intersexual proxies; visual-arts did not have predictors. Although present in both sexes, each sexual selection component has different relative importance in each sex. Artisticality function to attract and maintain long/short-term partners, and to compete with mating rivals.